Kebenaran: Keadilan dan Kejujuran menurut Mazmur 111 - Purba, Jhon Leonardo Presley; Widodo, Priyantoro (Sekolah Tinggi Teologi Kalvari Manado, 2023)
Abstract: Truth is not just a conception of idealism in the mind but also a real and concrete experience in human life. As seen in the text of Psalm 111, the psalmist writes of praise and his real experience of God's truth. Using a descriptive-qualitative approach with literature study methods and hermeneutic exegesis, this study aims to understand the real and concrete meaning of God's truth, which is manifested in the form of justice and integrity as contained in the text of Psalm 111. The results of this study conclude that based on the text and context of Psalm 111, we get the theological concept of God's truth, which is manifested in real and concrete justice and integrity in the spiritual and actual experience of human life through God's righteous, just, straight, honest, and wise actions toward humans. This has anthropological implications for human actions that are right, fair, straight, honest, and wise horizontally towards others, which the psalmist stated concretely through his caring attitude towards the poor and being willing to give or share with fellow human beings in his day. These attitudes and actions are imitations of God's character. Right attitudes and actions in the form of justice and integrity are absolute and universal, so they are relevant to be applied horizontally in today's human life, especially for believers who have faith in Christ. As the New Testament emphasizes the transformation and renewal of man into the image and likeness of God through faith in Christ and the likeness of Christ's character, so today's believers must care for the poor, be willing to share with others in need, and have integrity in their horizontal relationships with others.Abstrak: Kebenaran bukan hanya sekedar konsepsi idealisme dalam pikiran tapi juga pengalaman nyata dan konkrit dalam kehidupan manusia. Sebagaimana tampak dalam teks Mazmur 111, pemazmur menuliskan pujian dan pengalamannya yang nyata atas kebenaran Tuhan. Menggunakan pendekatan kualitatif deskriptif dengan metode studi literature dan hermeneutik-eksegeses, penelitian ini bertujuan untuk memahami makna kebenaran Tuhan yang rill dan konkrit yang termanifestasi dalam wujud keadilan dan kejujuran sebagaimana yang terdapat dalam teks Mazmur 111. Hasil dari penelitian ini menyimpulkan bahwa berdasarkan teks dan konteks Mazmur 111 didapatkan konsep teologis kebenaran Tuhan yang diwujudkan dalam keadilan dan kejujuran yang nyata dan konkrit dalam pengalaman spiritual dan aktual hidup manusia melalui tindakan-tindakan benar, adil, lurus, jujur, dan bijaksana Tuhan kepada manusia. Hal ini berimplikasi secara antropologis terhadap tindakan-tindakan manusia yang benar, adil, lurus, jujur, dan bijaksana secara horizontal terhadap sesamanya yang dinyatakannya secara konkrit oleh pemazmur melalui sikap peduli terhadap orang miskin dan rela memberi/berbagi dengan sesama manusia pada zamanya. Sikap dan tindakan ini merupakan peniruan atas karakter Tuhan. Sikap dan tindakan benar dalam wujud adil dan jujur ini bersifat absolut dan universal sehingga relevan diterapkan secara horizontal dalam kehidupan manusia masa kini, khususnya orang percaya yang beriman kepada Kristus. Sebagaimana Perjanjian Baru menekankan transformasi dan pembaharuan manusia menuju gambar dan keserupaan dengan Allah melalui iman kepada Kristus dan keserupaan dengan karakter Kristus, karenanya orang percaya masa kini harus perduli terhadap orang miskin, rela berbagi dengan sesama yang membutuhkan dan jujur/berintegritas dalam hubungan horizontal dengan sesamanya.